For any square matrix, we define
(i) A1 = A and (ii) An+1 = AnA, where n is positive integers, (n ∈ N).
It is clear from the above definitions that A2 = AA; A3 = A2A = (AA)A etc.
Similarly AmAn = Am+n
and (Am)n = Amn, where m, n ∈N
Matrix Polynomial:
If f(x) = a0An + a1xn-1 + a2xn-2 + .......... + an-1x + an is a polynomial and A is a square matrix of
order n. Then
f(A) = a0An + a1An-1 + a2An-2 + ............ + an-1A + anIn
is called a matrix polynomial
Example: If f{x) = x3 + 3x2 - 3x + 2 be a polynomial and is a square matrix, then
f(A) = A3 + 3A2 - 3A + 21 is a matrix polynomial.
Theorem 1.
If A and B are two matrices of same order, then
(A + B)2 = A2 + AB + BA + B2 When AB = BA then (A + B)2 = A2 + 2AB + B2
Proof:
Let A and B are two matrices of same order n.
Thus, (A + B) is a square matrix of order n
Now, (A + B)2 = (A + B) (A + B)
= A(A + B) + B(A + B) (By distributive law)
= AA + AB + BA + BB (By distributive law)
= A2 + AB + BA + B2
Thus (A + B)2 = A2 + AB + BA + B2 ...(i)
Special case: When AB = BA, then
(A + B)2 = A2 + AB + BA + B2 [From(i)]
= A2 + AB + AB + B2 (∵ AB = BA)
= A2 + 2AB + B2
Thus (A + B)2 = A2 + 2AB + B2
Theorem 2.
If A and B are two matrices of same order, then
(A + B) (A - B) = A2 - AB + BA - B2 when
AB = BA, then (A + B) (A - B) = A2- B2
Proof:
(A + B) (A - B) = A(A - B) + B(A - B) (By law of distribution)
= AA -AB + BA - BB (By law of distribution)
= A2 - AB + BA - B2
Thus, (A + B) (A - B) = A2 - AB + BA - B2 ...(i)
Special case: When AB = BA then,
(A + B) (A - B) = A2 - AB + AB - B2, From (i)
= A2 - B2 (∵ AB = BA)
Therefore, (A + B) (A - B) = A2 - B2